The Collapse Of The Symbolic Order: A Lacanian Psychoanalysis Of The Mother Figure In The Movie Norma: Antara Mertua Dan Menantu - Nuri Adlina; Desthia Amalia (Asosiasi Dosen Muda Indonesia, 2026)
The mother figure in Indonesian families is traditionally constructed as the guardian of moral values. However, the movie Norma: Antara Mertua dan Menantu depicts a radical deviation where a mother engages in an incestuous relationship with her son-in-law. This study aims to analyze the psychic dynamics of the mother character, Rina, using Jacques Lacan's psychoanalytic theory. Using a qualitative descriptive method, this research dissects visual and verbal data representing the three Lacanian registers: The Real, The Imaginary, and The Symbolic. The results indicate that Rina's transgression is not merely a moral failure but a structural collapse of the Symbolic order caused by the absence of